The attention markets as a challenge for competition policy - Drobny, Paweł (Rynki uwagi jako wyzwanie dla polityki konkurencji, 2019)
The article concerns a problem from the border of competition policy, economics and business. The practices of companies such as Facebook, which dominate the attention markets, have sparked a discussion about the effectiveness of traditional competition policy. The aim of the work is an attempt to indicate that the nature of the object of exchange and the specificity of these monopolized markets require changes in antitrust policy. The first part characterizes the attention markets and the nature of the object of exchange. The second part characterizes the traditional competition policy. The third part presents arguments in the current discussion on the effectiveness of competition policy and presents proposals for technical changes in this policy. Then, presents arguments that the discussion should primarily concern fundamental changes and indicates the need to change the approach to attention markets and broaden the criteria for assessing anti-competitive practices by criteria for assessing their human dimension
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 5, s. 29-42
Keywords: competition policy; attention; attention market; two-sided platform; digital economy; polityka konkurencji; uwaga; rynek uwagi; platforma dwustronna; gospodarka cyfrowa